Respuesta :
STEP-BY-STEP SOLUTION:
= x^2 - 13x + 30
= x^2 - 10x - 3x + 30
= x ( x - 10 ) - 3 ( x - 10 )
= ( x - 10 ) ( x - 3 )
FINAL ANSWER:
Therefore, the answer is:
C. x - 10
Please mark as brainliest if you found this helpful! :)
Thank you and have a lovely day! <3
= x^2 - 13x + 30
= x^2 - 10x - 3x + 30
= x ( x - 10 ) - 3 ( x - 10 )
= ( x - 10 ) ( x - 3 )
FINAL ANSWER:
Therefore, the answer is:
C. x - 10
Please mark as brainliest if you found this helpful! :)
Thank you and have a lovely day! <3
The correct answer is Option (C) x-10
What is Binomial Equation?
- The expression having two terms is known as binomial equation.
What is trinomial equation?
- The equation having three terms is known as trinomial equation.
How to Solve this question?
The equation is solved by following steps
The equation given is x2 - 13x + 30
We need to find the binomial factor of this trinomial equation
So, we will find the factor by splitting the middle term
[tex]x^{2} -13x+30\\=x^{2} -10x-3x+30\\=x(x-10)-3(x-10)\\=(x-10)(x-3)[/tex]
Hence the Binomial factor from the option is x-10
Therefore Option (c) is correct
Learn more about binomial here
https://brainly.com/question/13672615
#SPJ2